Synthesis, Characterization and Application of Polypyrrole Functionalized Nanocellulose for the Removal of Cr(VI) from Aqueous Solution - Norah Salem Alsaiari (MDPI AG, 2021)
Heavy metals are toxic substances that pose a real danger to humans and organisms, even at low concentration. Therefore, there is an urgent need to remove heavy metals. Herein, the nanocellulose (NC) was synthesized by the hydrolysis of cellulose using sulfuric acid, and then functionalized using polypyrrole (ppy) through a polymerization reaction to produce polypyrrole/nanocellulose (ppy/NC) nanocomposite. The synthesized nanocomposite was characterized using familiar techniques including XRD, FT-IR, SEM, TEM, and TGA. The obtained results showed a well-constructed nanocomposite with excellent thermal stability in the nano-sized scale. The adsorption experiments showed that the ppy/NC nanocomposite was able to adsorb hexavalent chromium (Cr(VI)). The optimum pH for the removal of the heavy metal was pH 2. The interfering ions showed minor effect on the adsorption of Cr(VI) resulted from the competition between ions for the adsorption sites. The adsorption kinetics were studied using pseudo 1st order and pseudo 2nd order models indicating that the pseudo second order model showed the best fit to the experimental data, signifying that the adsorption process is controlled by the chemisorption mechanism. Additionally, the nanocomposite showed a maximum adsorption capacity of 560 mg/g according to Langmuir isotherm. The study of the removal mechanism showed that Cr(VI) ions were removed via the reduction of high toxic Cr(VI) to lower toxic Cr(III) and the electrostatic attraction between protonated ppy and Cr(VI). Interestingly, the ppy/NC nanocomposite was reused for Cr(VI) uptake up to six cycles showing excellent regeneration results. Subsequently, Cr(VI) ions can be effectively removed from aqueous solution using the synthesized nanocomposite as reusable and cost-effective adsorbent.